Engineering natural and noncanonical nicotinamide cofactor-dependent enzymes: design principles and technology development. (December 2020) - King, Edward; Maxel, Sarah; Li, Han
Graphical abstract: Abstract : Nicotinamide cofactors enable oxidoreductases to catalyze a myriad of important reactions in biomanufacturing. Decades of research has focused on optimizing enzymes which utilize natural nicotinamide cofactors, namely nicotinamide adenine dinucleotide (phosphate) (NAD(P) + ). Recent findings reignite the interest in engineering enzymes to utilize noncanonical cofactors, the mimetics of NAD + (mNADs), which exhibit superior industrial properties in vitro and enable specific electron delivery in vivo . We compare recent advances in engineering natural versus noncanonical cofactor-utilizing enzymes, discuss design principles discovered, and survey emerging high-throughput platforms beyond the traditional 96-well plate-based methods. Obtaining mNAD-dependent enzymes remains challenging with a limited toolkit. To this end, we highlight design principles and technologies which can potentially be translated from engineering natural to noncanonical cofactor-dependent enzymes.